2022
DOI: 10.3389/fcimb.2022.784130
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Bacterial Infection and Clinical Characteristics in Patients With COVID-19 Admitted to Two Intensive Care Units of an Academic Hospital in Iran During the First Wave of the Pandemic

Abstract: Data on the prevalence of bacterial co-infections and secondary infection among adults with COVID-19 admitted to the intensive care unit (ICU) are rare. We aimed to determine the frequency of secondary bacterial infection, antibiotic use, and clinical characteristics in patients admitted to the ICU with severe SARS-CoV-2 pneumonia. This was a retrospective cohort study of adults with severe COVID-19 admitted to two ICUs from March 6 to September 7, 2020 in an academic medical center in Isfahan, Iran. To detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 22 publications
5
66
0
1
Order By: Relevance
“…In line with previous studies, 6 , 8 , 13 , 16 , 18 a higher mortality was observed in patients who suffered from secondary infection. A significant association was found between secondary bacterial infection and mortality, of which 65.7% deaths were reported.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous studies, 6 , 8 , 13 , 16 , 18 a higher mortality was observed in patients who suffered from secondary infection. A significant association was found between secondary bacterial infection and mortality, of which 65.7% deaths were reported.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, several studies observed an increased occurrence of gram-negative organisms as opposed to gram-positive. 6 , 14 , 16–18 In line with Musuuza et al, 6 the most prevalent pathogens in the current study were P. aeruginosa and A. baumannii . Secondary infection of the respiratory system was the most common followed by bloodstream infection.…”
Section: Discussionsupporting
confidence: 87%
“…Several complications can arise during ICU stay, from both COVID-19 extensive lung damage and extra-pulmonary involvement, as well as those secondary to mechanical supporting systems [ 2 , 3 , 4 , 5 , 6 ]. Among these, bacterial and fungal co-infections and superinfections (or secondary infections) play an important role in COVID-19 disease and have been associated with increased morbidity and mortality, especially in critically ill patients [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the secondary infections Secondary infections were identified by infection that developed during ICU stay but after admission of more than 48 h duration, meaning not present at the time of presentation with COVID-19. 13 …”
Section: Methodsmentioning
confidence: 99%
“…For the secondary infections Secondary infections were identified by infection that developed during ICU stay but after admission of more than 48 h duration, meaning not present at the time of presentation with COVID-19. 13 Exclusion criteria: Patients tested negative/inconclusive for SARS-COV-2 infection and those patients tested positive for SARS-COV-2, but not hospitalized.…”
Section: Study Populationmentioning
confidence: 99%